Hidroformilação/aminação redutiva de olefinas biorrenováveis: síntese de novos produtos com potencial aplicação farmacológica - Adelson de Oliveira Dias (2019)
The class of amines represents important intermediates in the synthesis of pharmaceuticals, agrochemicals, surfactants and other fine chemical products. However, the production of these compounds is performed industrially by means of reactions that often use toxic reagents and generate large amounts of waste. The hydroaminomethylation is a tandem catalytic process comprised of three steps: hydroformylation of alkene, resulting in an aldehyde; Amine condensation with aldehyde and hydrogenation of the enamine or imine formed in the second stage.This reaction aligns to the precepts of green chemistry, since it is very selective and usually generates few secondary products. So, in this work, it was possible to perform the synthesis of amines structurally complex, with potential biological activity, from bio-renewable substrates and low cost. The hydroaminomethylation of biorenewable substrates -pinene, camphene and limonene, catalyzed by rhodium complexes, with secondary amines, Morpholine, 4-methylpiperidine and 1,2,3,4-tetrahydroisoquinoline, is optimized through the variation of the main reactional parameters, namely, catalytic precursor/ligand, temperature, structure of the ligand, amount of catalyst. By means of this catalytic process, were synthesized, single-step, new amines derived from the -pinene, a challenging substrate, due to the ease of isomerizationof your structure, with greater than 50% conversions and selectivity of around 80% for amine interest, when using the solvent toluene. However, in ethanol, an environmentally friendly solvent less impactful and economically cheaper, and in the presence of the phosphite p (o-otbuph)3 (TBPP), the conversions of the substrate were greater than 95% and with selectivity for the amine end more than 65%. In thisway, the use of ethanol allowed not only increase the reaction yield as promoting a more sustainable process. The hydroaminomethylation in toluene of limonene and camphene led to conversions in excess of 99%, with greater than 90% selectivity. A similar result was obtained when using the TBPP phosphite in ethanol. Therefore, ethanol represents a greener alternative to the toluene, solvent commonly used in cases of hydroaminomethylation.